IRAN’S FOREIGN POLICY IN THE CASPIAN SEA BASIN Oscillation between National Interests and Islamic Adventures - BEHZADI, Raheleh (CENTRAL ASIA AND THE CAUCASUS, 2010)
The Caspian Sea Basin is considered one of the largest energy reserves in the world. The subsoil of this immense land-locked sea has become a serious bone of contention among the littoral states grappling with the Caspian Sea legal regime. Despite the Alma-Ata Declaration of 1991, the new coastal states—Kazakhstan, Azerbaijan, and Turkmenistan—rejected the 1921 and 1940 treaties between Iran and the Soviet Union and insisted on creating a new legal regime. At the third summit of the five Caspian Sea littoral states in Tehran on 16 October, 2007, Kazakhstan President Nursultan Nazarbaev stated that the 1921 and 1940 treaties between Iran and the Soviet Union on the Caspian Sea now belong to history.1 Moreover, in January 2008, Iranian Foreign Minister Manoochehr Mottaki said that Iran’s share of the Caspian Sea has never been 50%, and the Soviet Union never allowed Iran to pass the hypothetical line. He added that Iran has never exploited more than 11.3% of the Caspian Sea. Although these explicit declarations angered the Iranian parliament and prompted an immediate response by Foreign Ministry Spokesman Hosseini, who specified that Iran’s share of the Caspian Sea is no less than 20 percent, this incident showed that the Iranian government has accepted the division of the Caspian Sea based on the median line method contrary to national drives.2 The pertinent question is why the Iranian government accepted the division of the Caspian Sea based on the median line, while Presidents Rafsanjani and Khatami insisted on the condominium regime or equal division? What priority is Iranian foreign policy pursuing that has overshadowed the importance of the Caspian Sea legal regime?